Do gender differences in upper body exercise among cross-country skiers increase with increasing intensity - Hegge, A. M.; Myhre, K.; Welde, B.; Holmberg, H. C.; Sandbakk, O. (2015)
Gender differences in upper body poling among cross - country skiers were greater than those previously observed for lower and whole body endurance exercise and increased with increasing intensity The gender differences in maximal aerobic capacity could not explain all differences in upper body poling performance, indicating that maximal strength and anaerobic capacity further differentiate gender in upper body performance This is supported by the greater work generated per cycle and larger distribution of mass in the upper body among male skiers. Additionally, male skiers reported to train larger volumes of upper body strength and endurance training Furthermore, the larger range of motion of the trunk during upper body poling shows that men and women use different techniques to increase the work rate Overall, our results indicate that female skiers have great potential to develop their upper body and would benefit from incorporating more upper body strength and endurance training into their training program